PERSEPSI PROFESI AKUNTAN TERHADAP PENERAPAN MANAJEMEN LABA - Mubarok, Abdulloh; Utami, Yuni (CERMIN, 2011)
This study aimed to determine ( 1 ) how perceptions of the accounting profession ( lecturer , management accountants and students ) to the application of earnings management and ( 2 ) whether there are significant differences in perceptions between faculty , management accountants and students of the management application . Data were collected by questionnaire survey techniques and produce 63 research respondents consisting of 10 accounting lecturer , management accounting 18 and 35 accounting students . The selection of respondents ( sample ) conducted convenience . Validity test performed by bivariate correlation between each indicator score , while reliability test performed with Cronbach alpha statistic test . To find out how well the perception of the accounting profession ( lecturer , management accountants and students ) to the application of earnings management , the data were analyzed with a total score of memproporsikan calculation of each group of respondents with a total score ideally . Then interpreted by the criteria of interpretation of the score. To determine whether there are significant differences between the two groups was conducted using Analysis of Variance ( ANOVA ) with post hoc tests derivative test , SPSS 16 for Windows . The results showed that in general the accounting profession ( lecturer , management accountants and students ) have a negative perception of earnings management application . Third of the accounting profession , the profession 's most lecturers have a good perception ( 84.92 % ) compared to the management accounting profession and students . The study also found that there are differences in the perception of earnings management practices between management accountants with lecturers and students , whereas for the management accounting profession with students did not reveal any differences in perception . Nevertheless for the accounting profession in the three groups did not reveal any difference in the average perception is significant about the application of earnings management .Keywords : perception , professional accountants , lecturers , management accountants , students , management earnings